2012
DOI: 10.5194/cp-8-373-2012
|View full text |Cite
|
Sign up to set email alerts
|

Climate variability of the mid- and high-latitudes of the Southern Hemisphere in ensemble simulations from 1500 to 2000 AD

Abstract: Abstract.To increase the sparse knowledge of long-term Southern Hemisphere (SH) climate variability, we assess an ensemble of 4 transient simulations over the last 500 yr performed with a state-of-the-art atmosphere ocean general circulation model. The model is forced with reconstructions of solar irradiance, greenhouse gas (GHG) and volcanic aerosol concentrations. A 1990 control simulation shows that the model is able to represent the Southern Annular Mode (SAM), and to some extent the South Pacific Dipole (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Before the influence of human-induced climate change became noticeable, the climate of the Southern Hemisphere mid-and high-latitudes was controlled by natural variability as well as volcanic and solar forcing. Over the past 500 years, the most noticeable change in the climate of the extratropical Southern Hemisphere has been a shift towards the positive phase of the Southern Annular Mode (Wilmes et al 2012). A study that has a similar goal to ours, Richard et al (2013), examined temperature trends from 1973-2002 and found a robust warming in sub-Antarctic and mid-latitude stations (Orcadas, Kerguelen, Marion, etc).…”
Section: Temperature Trends In the Extratropical Southern Hemispherementioning
confidence: 74%
“…Before the influence of human-induced climate change became noticeable, the climate of the Southern Hemisphere mid-and high-latitudes was controlled by natural variability as well as volcanic and solar forcing. Over the past 500 years, the most noticeable change in the climate of the extratropical Southern Hemisphere has been a shift towards the positive phase of the Southern Annular Mode (Wilmes et al 2012). A study that has a similar goal to ours, Richard et al (2013), examined temperature trends from 1973-2002 and found a robust warming in sub-Antarctic and mid-latitude stations (Orcadas, Kerguelen, Marion, etc).…”
Section: Temperature Trends In the Extratropical Southern Hemispherementioning
confidence: 74%
“…F10 Ī“D has been correlated with 2 m wind fields from ERA-Interim ( Figure 3b) to confirm that warm (less negative Ī“D) years are associated with strengthening of the meridional winds (onshore northerlies) between~50-70Ā°S,~100-140Ā°W (contours in Figure 3b). This pattern is maintained in the longer reanalysis data sets, including GISS [Hansen et al, 2010 [Wilmes et al, 2012].…”
Section: What Is Driving the Recent Isotopic Warming?mentioning
confidence: 75%
“…Comparatively little attention has been given to the Southern Hemisphere, or to South America specifically (although see Joseph andZeng, 2011, andWilmes et al, 2012). Some previous work has focused on the Southern Annular Mode in the ERA-40 and NCEP/NCAR reanalysis, in addition to a previous version of NASA Goddard Institute for Space Studies (GISS) Model-E (Robock et al, 2007) and in a subset of CMIP3 models (Karpechko et al, 2010) or in CMIP5 (Gillett and Fyfe, 2013).…”
Section: Volcanic Forcing On Climatementioning
confidence: 99%